Intrinsic disorder in the partitioning protein KorB persists after co-operative complex formation with operator DNA and KorA - Hyde, Eva I.; Callow, Phillip; Rajasekar, Karthik V.; timmins, Peter; Patel, Trushar Patel; Siligardi, Giuliano; Hussain, Rohanah; White, Scott A.; Thomas, Christopher M.; Scott, David J. (Portland Press, 2017)
The ParB protein, KorB, from the RK2 plasmid is required for DNA partitioning and transcriptional repression. It acts co-operatively with other proteins, including the repressor KorA. Like many multifunctional proteins, KorB contains regions of intrinsically disordered structure, existing in a large ensemble of interconverting conformations. Using NMR spectroscopy, circular dichroism and small-angle neutron scattering, we studied KorB selectively within its binary complexes with KorA and DNA, and within the ternary KorA/KorB/DNA complex. The bound KorB protein remains disordered with a mobile C-terminal domain and no changes in the secondary structure, but increases in the radius of gyration on complex formation. Comparison of wild-type KorB with an N-terminal deletion mutant allows a model of the ensemble average distances betweenthe domains when bound to DNA. We propose that the positive co-operativity between KorB, KorA and DNA results from conformational restriction of KorB on binding each partner, while maintaining disorder.